Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.3390/ijms23147851
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Putative Acylated Cellulose Synthase Operon in Komagataeibacter xylinus E25

Abstract: Bacterial cellulose is a natural polymer with an expanding array of applications. Because of this, the main cellulose producers of the Komagataeibacter genus have been extensively studied with the aim to increase its synthesis or to customize its physicochemical features. Up to now, the genetic studies in Komagataeibacter have focused on the first cellulose synthase operon (bcsI) encoding the main enzyme complex. However, the role of other accessory cellulose operons has been understudied. Here we aimed to fil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 57 publications
0
7
0
Order By: Relevance
“…This technique with simplicity and rapidness can be deployed for synthesis of BC under mild conditions (Figure ). Recent studies have demonstrated the fabrication of BC-based functional biomaterials regulated at the molecular level through different mechanisms, including cellulose synthase operon ( bcsI ) as well as plasmid-based expression system. ,, …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This technique with simplicity and rapidness can be deployed for synthesis of BC under mild conditions (Figure ). Recent studies have demonstrated the fabrication of BC-based functional biomaterials regulated at the molecular level through different mechanisms, including cellulose synthase operon ( bcsI ) as well as plasmid-based expression system. ,, …”
Section: Introductionmentioning
confidence: 99%
“…48 Recent studies have demonstrated the fabrication of BC-based functional biomaterials regulated at the molecular level through different mechanisms, including cellulose synthase operon (bcsI) as well as plasmid-based expression system. 20,53,54 Several studies have focused on the biomedical applications, properties, and fabrication methods of BC-based materials. 55−57 However, the present review aims to provide a great insight into promising green nanotechnology approaches in cardiovascular TE, particularly the most recent developments pertaining to the cardiovascular TE applications of BC-based materials.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the colonization of biotic and abiotic surfaces by some opportunistic human and plant pathogens has been linked to the production of biofilms composed of the β-(1→4)-linked d -glucose polymer, cellulose. A growing list of bacteria, including Acetobacter ( 11 , 12 ), Clostridium (previously Sarcina ) ( 6 , 11 ), Bordetella ( 13 ), Komagataeibacter ( 13 ), Rhizobium ( 11 ), Agrobacterium ( 11 ), Cronobacter ( 5 ), Salmonella ( 14 ), Escherichia coli ( 15 , 16 , 17 ), and Pseudomonas ( 18 ), are now known to produce cellulose and are of clinical and economical importance. Of the organisms on this list, E. coli and Salmonella enterica are the most extensively studied with respect to bacterial cellulose biosynthesis and have served as model organisms for understanding the synthesis and export of the polymer ( 3 , 16 , 17 , 19 ).…”
mentioning
confidence: 99%
“…WssD is a predicted glycoside hydrolase, like BcsZ from E. coli and CcsZ from Clostridium difficile , and is proposed to cleave the growing polymer to allow release from the cell into the biofilm matrix ( 46 , 50 , 53 , 54 ). While the downstream wssFGHI genes (or homologs thereof) are beginning to be noted with cellulose synthase systems, the biochemical activity of the individual gene products remain uncharacterized ( 12 , 55 ). However, these gene products share homology to algX/FIJ , which contribute to acetylation of alginate in P. aeruginosa , so wssFGHI are likewise predicted to encode for proteins that decorate the cellulose polymer with acetyl groups in an analogous fashion.…”
mentioning
confidence: 99%
See 1 more Smart Citation